2018
DOI: 10.1192/bjp.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nature-based therapy for individuals with stress-related illnesses: randomised controlled trial

Abstract: The study showed no statistical evidence of a difference between NNBT and STreSS for treating patients with stress-related illnesses.Declaration of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Choosing an ecovillage in the countryside as a setting for the intervention was therefore believed to be important. Based on our findings, we also proposed that there is evidence for the positive impact of a nature environment and horticultural or nature-based activity on mental health, which is in line with the findings of other studies [ 61 , 62 , 63 , 64 ]. Due to their poor mental health, some of the participants needed an even more sheltered environment to support their mental restoration such as a sheltered therapeutic garden.…”
Section: Discussionsupporting
confidence: 91%
“…Choosing an ecovillage in the countryside as a setting for the intervention was therefore believed to be important. Based on our findings, we also proposed that there is evidence for the positive impact of a nature environment and horticultural or nature-based activity on mental health, which is in line with the findings of other studies [ 61 , 62 , 63 , 64 ]. Due to their poor mental health, some of the participants needed an even more sheltered environment to support their mental restoration such as a sheltered therapeutic garden.…”
Section: Discussionsupporting
confidence: 91%
“…The results from the background questionnaire showed that the vast majority of participants were women (NBT: 82%, CBT: 82%) with a mean age of 47.9 in NBT and 44.9 in CBT [ 11 ]. The majority had a university bachelor degree or higher education (NBT: 76%, CBT: 68%).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the participants in the NBT and the CBT still caused greater healthcare costs in regard to this variable when compared to the general population. It was decided to focus only on the variable “number of contacts with a GP” concerning healthcare consumption, because this was stated by the participants as their most common personal re-habilitation initiative prior to treatment [ 11 ]. No participants were hospitalized prior to treatment due to stress-related illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations